Native American Educational Leader Preparation: The Design and Delivery of an Online Interdisciplinary Licensure Program - Linda R. Vogel; Harvey Rude (Educational Considerations, 2010)
In a 1991 report, the Indian Nations at Risk Task Force documented a lack of Native educators as role models for Native American students and set a goal of doubling their number by the year 2000.
Keywords: Native American; educational; leader; design; delivery; interdisciplinary; Licensure Program; impairments; multicultural; children